T‐NET, a dynamic model for simulating daily stream temperature at the regional scale based on a network topology. Issue 13 (23rd February 2016) - Beaufort, A.; Curie, F.; Moatar, F.; Ducharne, A.; Melin, E.; Thiery, D.
Abstract: Currently, the distribution areas of aquatic species are studied by using air temperature as a proxy of water temperature, which is not available at a regional scale. To simulate water temperature at a regional scale, a physically based model using the equilibrium temperature concept and including upstream‐downstream propagation of the thermal signal is proposed. This model, called Temperature‐NETwork (T‐NET), is based on a hydrographical network topology and was tested at the Loire basin scale (10 5  km 2 ). The T‐NET model obtained a mean root mean square error of 1.6 °C at a daily time step on the basis of 128 water temperature stations (2008–2012). The model obtained excellent performance at stations located on small and medium rivers (distance from headwater <100 km) that are strongly influenced by headwater conditions (median root mean square error of 1.8 °C). The shading factor and the headwater temperature were the most important variables on the mean simulated temperature, while the river discharge influenced the daily temperature variation and diurnal amplitude. The T‐NET model simulates specific events, such as temperature of the Loire during the floods of June 1992 and the thermal regime response of streams during the heatwave of August 2003, much more efficiently than a simple point‐scale heat balance model. The T‐NET model is very consistent at a regional scale and could easily be transposed to changing forcing conditions and to other catchments. Copyright © 2016 John Wiley & Sons, Ltd.